2005
DOI: 10.1152/ajplung.00135.2004
|View full text |Cite
|
Sign up to set email alerts
|

SP-A1 and SP-A2 variants differentially enhance association ofPseudomonas aeruginosawith rat alveolar macrophages

Abstract: aeruginosa. Two genes, SP-A1 and SP-A2, encode human SP-A. We hypothesized that genetically determined differences in the activity of SP-A1 and SP-A2 gene products exist. To test this, we studied association of a nonmucoid P. aeruginosa strain (ATCC 39018) with rat alveolar macrophages in the presence or absence of insect cellexpressed human SP-A variants. We used two trios, each consisting of SP-A1, SP-A2, and their coexpressed SP-A1/SP-A2 variants. We tested the 6A 2 and 6A 4 alleles (for SP-A1), the 1A 0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
128
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(141 citation statements)
references
References 70 publications
(94 reference statements)
10
128
1
2
Order By: Relevance
“…Moreover, qualitative and quantitative differences have been observed in vitro between the SP-A1 and SP-A2 genes (22,36,57,60,(77)(78)(79)(80)(81), pointing to the possibility that the overall functional activity of SP-A may depend on the relative SP-A1-to-SP-A2 levels rather than on the total SP-A content. To address this possibility, it .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, qualitative and quantitative differences have been observed in vitro between the SP-A1 and SP-A2 genes (22,36,57,60,(77)(78)(79)(80)(81), pointing to the possibility that the overall functional activity of SP-A may depend on the relative SP-A1-to-SP-A2 levels rather than on the total SP-A content. To address this possibility, it .…”
Section: Discussionmentioning
confidence: 99%
“…More than 30 alleles have been characterized for these two genes, with four SP-A1 alleles (6A, 6A 2 , 6A 3 , and 6A 4 ) and six SP-A2 alleles (1A, 1A 0 , 1A 1 , 1A 2 , 1A 3 , and 1A 5 ) most frequently observed in the general population (10,14,16,40,67). Although a high level of sequence similarity is shared among the SP-A genes and their corresponding alleles, in vitro studies have identified both qualitative (22,36,57,60,77,80,81) and quantitative (24,35,38,46,56,69,70,78,79) differences between the two genes.Qualitative differences between the SP-A1 and SP-A2 genes include functional, structural, and biochemical differences. Functionally, SP-A2 exhibits a higher level of activity than SP-A1 in its ability to enhance TNF-␣ and IL-8 production by the macrophage-like THP-1 cell line (80, 81), phagocytosis of Pseudomonas aeruginosa by rat alveolar macrophages (57), and secretion of phosphatidylcholine by type II alveolar cells (77).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…включают их способность стимулировать фагоцитоз [12,14], ин-гибировать секрецию сурфактанта [15], стимулировать продук-цию α-фактора некроза опухоли (TNF-α) [16], как и различия в их аггрегации и олигомеризации [15].…”
Section: терапевтический архив 1 2015unclassified
“…Показано, что SP-A воздействует на рост и жизнеспособность микроорга-низмов, повышая проницаемость микробной клеточной мембра-ны [3], регулирует механизмы иммунной защиты в легких путем связывания звеньев врожденного и приобретенного компонен-тов иммунитета [4], стимулирует хемотаксис макрофагов [5], вли-яет на пролиферацию клеток иммунного ответа и на продукцию провоспалительных цитокинов [6,7], повышает продукцию ре-активных оксидантов [8], регулирует продукцию оксида азота [9], стимулирует фагоцитоз [10][11][12].…”
unclassified